Joseph C. Swidler papers - Swidler, Joseph C. (Joseph Charles), 1907-1997.
Correspondence, memoranda, reports, speeches, business and legal files, transcripts of congressional hearings, autobiographical material, oral history transcript, printed matter, and other papers documenting Swidler's career as a lawyer specializing in the regulation of the public power system. Includes material on his service with the Tennessee Valley Authority, Federal Power Commission, the electric power failure in the Northeastern states (1965), New York Public Service Commission, National Association of Regulatory Utility Commissioners, Institute for Public Policy Alternatives, U.S. Atomic Energy Commission, International Conference on Water for Peace, a United Nations seminar on international utilization of water resources, and various private law firms. Topics include the creation of a continental power grid, loyalty hearings with regard to the Tennessee Valley Authority employees' alleged connections with the Communist Party, and the infrastructural and energy supply crises of the 1960s and 1970s.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Lawyer and public power industry regulatory official.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Institute for Public Policy Alternatives; National Association of Regulatory Utility Commissioners; New York (State). -- Public Service Commission; Tennessee Valley Authority; U.S. Atomic Energy Commission; United Nations; United States. -- Federal Power Commission; Allegiance; Electric power failures -- Northeastern States; Energy policy -- United States; Interconnected electric utility systems -- United States; Lawyers -- United States; Loyalty; Power resources -- Law and legislation -- United States; Water resources development; New York (State) -- Politics and government; Lawyers; Public officials